Atrial Fibrillation and Heart Failure - Leonard Bergau (Journal of Clinical Medicine, 2022)
Atrial fibrillation (AF) is the most common sustained arrhythmia worldwide and has a strong association with heart failure (HF). It often remains unclear if HF is the cause or consequence of AF due to the complexity of the processes that are involved in both the perpetuation of AF and the development of HF. To date, two therapeutic strategies are accepted as the standard of care in AF patients with heart failure. Rhythm control aims to permanently restore sinus rhythm, whereas a rate-control strategy aims to slow ventricular rate without the termination of AF. In the last 5 years a tremendous number of important studies have been published investigating the optimal therapeutic strategy in HF patients. This review highlights the important studies with respect to the involvement of AF in promoting left-ventricular dysfunction and discusses the optimal strategy in HF patients suffering from AF.